β-1,3-Glucan Recognition Protein Can Inhibit the Proliferation of Bombyx mori Cytoplasmic Polyhedrosis Virus - Yinong Zhang; Jiming Yan; Yukai Xie; Xiong Wang; Feifei Ren; Haixu Bian; Jingchen Sun (Insects)
Insects detect pathogens through their germ-line encoded pattern recognition receptors (PRRs). Among these, β-1,3-glucan recognition protein (βGRP) is a crucial PRR that specifically identifies pathogenic microorganisms and triggers innate immune signaling cascades. However, it remains unclear whether βGRP can detect viruses and protect the host from viral threats. In this study, using high-throughput sequencing technology, we observed a significant suppression of βGRP-3 in Bombyx mori during infection with the Bombyx mori cytoplasmic polyhedrosis virus (BmCPV). Moreover, overexpression of βGRP-3 in BmN cell lines resulted in a reduction of BmCPV proliferation, whereas knockdown of βGRP-3 in BmN cells promoted BmCPV proliferation. These findings suggest that the βGRP family functions not only as anti-bacterial, antifungal, and anti-yeast PRRs but also as protectors against various harmful viruses in insects.